The dependency of an individual's and state well-being on higher education quality: analysis of Ukrainian students' and employers' opinion - Moroz, Svitlana; Moroz, Volodymyr; Kalagin, Yurii; Grygoryeva, Svitlana; Sutula, Oksana; Kozlova, Olena; Moroz, Oleksandr (ТОВ "Фінтехальянс", 2022)
Statistical information attests to the fact that the share of the Ukrainian population with higher education is one of the largest in the world and comprises more than 82%, which considerably surmounts corresponding indicators for countries with a high level of social and market institutes’ development. A large share of persons with higher education in Ukraine and a comparatively low dynamics of its socio-economic development rise a question of the relevance of the human capital theory for those countries that are currently at the stage of the so-called permanent social and economic transformation. The socio-economic results of such countries’ development suggest certain limitations of the human capital theory, namely those of its postulates whose contents imply the existence of a directly proportional dependency of an individual’s well-being at the level and quality of their education. The controversy between the theory and practices of investment in higher education, especially in the context of comparing an expected and the actual social and economic effect, has determined the need to clarify the opinion of represent-atives of the present-day society concerning the existence of cause-and-effect connections between quality of higher education and well-being. As an instrument for collecting information on the issue of dependency of an individual’s well-being and that of the state on the quality of higher education, the method of polling was selected and applied in the form of a questionnaire. Representatives of student youth and employers from the eastern oblasts (areas) of Ukraine acted as respondents. On the results of the comparative analysis of 747 respondents’ answers, the authors of this article formulate generalizations and conclusions concerning the object of scientific interest. There is sub stantiated the expediency of introducing to the scientific circulation and further use of indicators of social and economic devaluation of higher education in practical activities for estimating state policy’s efficiency in the sphere of higher education.
Залежність добробуту особистості й держави від якості вищої освіти: аналіз думки студентів та роботодавців з України
Keywords: quality of higher education; human capital; investing in higher education; well-being of a social object; economic value of higher education; higher education coverage; polling students and employers; economic and social devaluation of higher education